Determinan Jumlah Penyaluran Pembiayaan Mudharabah pada Unit Usaha Syariah (UUS) di Indonesia Periode 2015-2022 - Ulya, Zikriatul; Hamid, Abdul; Armaya, Tika; Eliza, Zulfa; Sumarni, Mutia (Jurnal Samudra Ekonomika, 2025)
The purpose of this study was to determine the effect of non-performing financing, third party funds and profit sharing rates on the amount of UUS mudharabah financing disbursement in Indonesia. The data collection method used was quantitative. The sample of this study was all monthly report data in the form of financial ratio reports and business activity reports of Sharia Business Units in the 2015-2022 period totaling 96 data. The results of the study indicate that non- performing financing does not have a significant effect on the amount of UUS mudharabah financing disbursement in Indonesia. Third party funds have a positive and significant effect on the amount of UUS mudharabah financing disbursement in Indonesia. The profit sharing rate does not have a significant effect on the amount of UUS mudharabah financing disbursement in Indonesia. Non-performing financing, third party funds and the profit sharing rate simultaneously have a positive and significant effect on the amount of UUS mudharabah financing disbursement in Indonesia.